The musical tale. Analysis of its textual components, music and drawings for developing basic skills in Primary Education - de Vicente- Yagüe Jara, María Isabel; Guerrero Ruíz, Pedro (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
This article presents the results of the Innovation Teaching Project Creativity Networks. Our aims are to analyze the various collaborative classroom networks; explain its usefulness in current education systems; determine the adaptability of students to a collaborative network that includes several professors and identify the university teaching techniques that the students consider as the most useful and creative. The group of students with whom we launched the Innovation Project had a major innovative core: 46.3% of students accepted studying and learning through a new system that included several professors. We found out that the variety of teaching methods was the factor that attracted them the most to the project but; at the same time; the one that more insecure generated them. In an educational context as the Spanish; where the traditional teaching methods prevail; it’s difficult to change established habits. Projects like this demonstrate the need for flexibility in the structures of education to make it more proactive; more active or experimental about innovations and allow professors and students to change their roles. Although there is resistance from students to immediate assimilation of an educational innovation; observability; i.e.; implementation and treatment as such; and even the act of requesting the participation of innovators among students "links"; ends up increasing acceptance of innovations.